Penerapan Teknologi Informasi untuk Penyebaran Informasi dan Manajemen Data di Procarehapustato Klaten - Ardiansyah Ardiansyah; Habib Ismail; Mustofa Romadhani; Fian Pandu Cahyadi; Muh. Ikhlazul Jihad (Universitas Muhammadiyah Klaten, 2025)
Information technology has received many positive reactions in use in various sectors, including in the field of MSME empowerment. The era of technology, which is often referred to as the 4.0 era, people tend to use technology in their daily lives so that MSMEs are forced to keep up with the times. However, in reality there are still many MSMEs that still cannot keep up with these developments due to several factors such as access to marketing or broad dissemination of information, or the quality of human resources owned by MSMEs. Procare Klaten is an MSME engaged in tattoo removal services. The problems found at Procare remove tattoos in Klaten, namely: Information dissemination, registration process, human resources (HR). So that designing an information system that can be used to provide information online so that it can be accessed by the public at large and accommodate the registration process is a solution. Furthermore, FGDs and intense meetings were held to assist and provide knowledge related to the latest technology to increase the productivity of Procare's human resources